Histopathological Features and Diagnosis of Breast Cancer - Ghina Shadrina Rienti Sepestian; Fathul Djannah (Postgraduate, University of Mataram, 2024)
In Indonesia, the high number of breast cancer cases is not always followed by complete clinical and histopathological determination, even though clinical and histopathological staging is needed to determine the diagnosis and further management. Breast cancer is a malignant mass originates from the uncontrolled division of cells in breast tissue Breast cancer or mammary carcinoma is a lump that grows and develops abnormally in the cells and tissues located in the breast, such as the fat tissue and connective tissue in the breast, ducts and lobules. The histopathological examination procedure is that the patient must undergo a biopsy. Biopsy results can be used to diagnose breast cancer and also monitor the success of therapy. Mammary carcinoma can spread to surrounding tissue or to other organs through blood vessels. Breast cancer is the most common cancer in Indonesia. The prognosis of breast cancer is determined by the 5 years survival rate. The survival rate for cancer sufferers in Indonesia is low compared to other developing countries, namely 51.07%. This research is in the form of a literature review with 14 papers as references. The results obtained were that invasive ductal carcinoma was the most common mammary carcinoma and grade II-III was found to be the dominant grade.